Factors influencing islamic credit card holders / Nik Alis Rina Jamsari. - Jamsari, Nik Alis Rina (2019)
Credit card, one of the non-cash methods of payment, has grown exponentially. Credit card usually uses bank-advanced credit balance to make payments. Banks charge cardholders for using the credit payment system or on the basis of the balance owed outstanding. Riba can be charged based on the outstanding balances. The Islamic banks have packaged their cards on the basis of some Islamic transaction principles to avoid this riba. Islamic credit card is the one product that is in line with shariah which is avoid riba in the transaction and lower fee charge that make consumers use it. Therefore, this study is conducted to analyze the factors influencing Islamic credit card holders. The study utilizes a descriptive analysis through survey with UiTM Cawangan Selangor Kampus Puncak Alam staff. The findings of this study indicate that 107 (71.3%) staff use Islamic credit card because Islamic credit card do not have riba, easy to carry and it is a medium of transaction and the most preferred Islamic credit card is offered by Maybank.. However, the result could be used as guidance for Islamic bankers and others institution in promoting Islamic credit card as well as for improvement in the future with regard to Islamic credit card.